2002
DOI: 10.1002/biof.5520160303
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic rat tissue accumulation of nobiletin, a chemopreventive polymethoxyflavonoid, in comparison with luteolin

Abstract: Nobiletin (NOB), a polymethoxyflavonoid, is an effective anti-inflammatory and chemopreventive phytochemical found in citrus fruits. We compared the absorption and metabolism characteristics of NOB with those of luteolin (LT) in male SD rats. Each flavonoid (67.1 micromol/kg of body weight) was given separately by gastric intubation, and then concentrations were measured at 1, 4, and 24 hours after administration. In the digestive organs, NOB showed a notable tendency for localizing into the mucous membrane an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 18 publications
1
54
2
Order By: Relevance
“…Our current data shows that IC 50 value for pure zerumbone treated WEHI 7.2 wild type cells at all three time points were less than 4 µg/ml and therefore exhibit in vitro cytotoxic activity. This result is in agreement with previous studies where zerumbone was found to show cytotoxic and anti-proliferative activities towards actively dividing cell lines, including leukemia, hepatocarcinoma and colon carcinoma (Murakami et al, 2002;Xian et al, 2007;Sakinah et al, 2007). Besides, data obtained also suggested that the activity of zerumbone is dose-dependent but not time-dependent, as the viability of cells decreased with increased zerumbone concentration but there are no significant differences between the IC 50 values for all three time points.…”
Section: Cytotoxic Effects Of Zerumbonesupporting
confidence: 92%
See 1 more Smart Citation
“…Our current data shows that IC 50 value for pure zerumbone treated WEHI 7.2 wild type cells at all three time points were less than 4 µg/ml and therefore exhibit in vitro cytotoxic activity. This result is in agreement with previous studies where zerumbone was found to show cytotoxic and anti-proliferative activities towards actively dividing cell lines, including leukemia, hepatocarcinoma and colon carcinoma (Murakami et al, 2002;Xian et al, 2007;Sakinah et al, 2007). Besides, data obtained also suggested that the activity of zerumbone is dose-dependent but not time-dependent, as the viability of cells decreased with increased zerumbone concentration but there are no significant differences between the IC 50 values for all three time points.…”
Section: Cytotoxic Effects Of Zerumbonesupporting
confidence: 92%
“…Early studies revealed that ZER is able to suppress free radical generation and oxidative stress through induction of endogenous antioxidants, such as phase II xenobiotic metabolising enzymes, suppress proinflammation proteins and cancer cell proliferation. It is therefore suggested that this compound can be explored as cancer chemo preventive agent (Murakami et al, 1999(Murakami et al, , 2002(Murakami et al, , 2003Nakamura et al, 2004). ZER was further found to exhibit antiproliferative effects on various actively dividing cell lines, including HL-60 human leukemic cells and NB4 promyelocytic leukemic cells via phase G2/M cell cycle arrest (Huang et al, 2005;Xian et al, 2007).…”
Section: Zerumbonementioning
confidence: 99%
“…One is the citrus flavonoid nobiletin (5,6,7,8,3′,4′-hexamethoxyflavone), which was administered together with the unmethylated luteolin (5,7, 3′,4′-tetrahydroxyflavone) to rats at 25 mg/kg by intubation [34]. The nobiletin content in the liver and kidneys ranged from 2 to 6 μM, i.e.…”
Section: Metabolic Resistance Of Methoxylated Flavonesmentioning
confidence: 99%
“…21) On the other hand, there are not many reports on the biotransformation of nobiletin in animals. [22][23][24][25] Yasuda et al found a few demethylated metabolites in 24 h-urine of rats orally administered nobiletin and determined that a major metabolite is 4Ј-demethylated (4Ј-OH) nobiletin. 24) However, the mechanism which the biological activities mentioned above are exerted by a parent compound or its metabolites remains obscure.…”
mentioning
confidence: 99%